SIMILAR LANGUAGE POLICIES, DIFFERENT MANAGEMENT STYLES, DIFFERENT RESULTS: NIGERIA AND PAPUA NEW GUINEA IN COMPARISON - Olatunji S. O. (African Journal of Educational Management, 2021)
The mother tongue based multilingual policy in education is stipulated in the Nigerian National Policy on Education. This is a natural fall-out from the ample evidence in research that early education given in children’s mother tongues provides more solid foundations for commendable academic success later in life than that given in borrowed languages. Literature is, however, replete with evidence of widespread non-compliance with the policy among Nigerians who demonstrate inordinate preference for the English language. The neglect of the policy stipulation has been found to be responsible for the ever-increasing rate of mass failure of Nigerian students. Papua New Guinea that records high rate of compliance with the same language policy in education experiences better academic achievement of students. The paper thus compares and contrasts language policy, management and practice issues in Nigeria with Papua New Guinea because of both countries’ multilingual nature. Both similarities and dissimilarities are found in the language policy management styles of both countries. Papua New Guinea, sometimes referred to as PNG, is found to manage the plurilingual situation much better than Nigeria. The Papua New Guinean government is found to have practised its language policy implementation in accordance with the principles of Language Management Theory from the field of Linguistics and Human Relations Theory from the field of Management. But Nigeria seemed to have been completely oblivious of such theories in its approach to language policy formulation and implementation, hence the great difference in success levels. The implications of the findings for Nigeria are also considered to point the way forward for the nation.